Addressing Techniques of Liquid Crystal Displays. - Ruckmongathan, Temkar N. (Wiley, 2014)
Unique reference source that can be used from the beginning to end of a design project to aid choosing an appropriate LCD addressing technique for a given application This book will be aimed at design engineers who are likely to embed LCD drivers and controllers in many systems including systems on chip. Such designers face the challenge of making the right choice of an addressing technique that will serve them with best performance at minimal cost and complexity. Readers will be able to learn about various methods available for driving matrix LCDs and the comparisons at the end of each chap.